Governing urban diversity: Multi-scalar representations, local contexts, dissonant narratives. (July 2019) - Raco, Mike; Tasan-Kok, Tuna
In recent academic and urban policy writings the term urban diversity is usually understood, or discussed within the context of, increasing 'socio-cultural' diversity in cities or is explicitly connected to debates over immigration and demographic change. Although policy agendas follow certain common trends 'to deal with' the consequences of diversity, there is a lack of evidence-based research on how representations of diversity are mobilised and implemented by institutions of governance operating at multiple scales and how these narratives relate to each other. Policy-makers are faced with new dilemmas over how to govern and manage cities that are becoming increasingly diverse, on the one hand, and increasingly 'sensitive' to certain channels of flows of people (such as refugees), on the other. In some cases, city authorities promote the idea of inclusive diversity as a mark of modernisation and tolerance. In others, its recognition may be seen as a threat to an imagined social order and is perceived to be fuelling neo-assimilationist policies in many European Union cities. This special issue aims to fill this gap by providing evidence-based research outcomes that tackle different dimensions of the governance of diversity in cities. The principal aim of the research project, named DIVERCITIES, that underpins this collection was to critically assess evidence concerning the range of socio-economic outcomes that may emerge from the presence of greater urban diversity. DIVERCITIES has shown that city policy agendas across Europe are often more 'positive' towards diversity than national policies and media reports. Moreover, local policy initiatives, mostly formed at the bottom-up scale, sometimes as a cooperation between state and civic actors and sometimes as purely private or even individual arrangements, address the actual needs of certain population groups by acting as bridge-builders between public authorities and target groups. This collection aims to provide a clear understanding of how diversity is understood, operationalised and dealt with at different scales of policy-making. In focusing on European examples, it provides an important addition to a literature that has become Anglo-American focused, both in terms of the concepts and policy interventions.